Fertilisation Effect on Quantity of 0.01 M CaCl2 Soluble N-Forms in a Long-Term-Small-Plot Experiment - Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2003)
long-term experiments have an opportunity to investigate the effects of fertilization and plant nutrition. The paper reports the results achieved in the 39th years of a long-term-small-plot fertilisation and liming experiment set up on acidic sandy brown forest soil in the Nyírség region. From the 32 treatment, four replications, altogether 128 plot experiments with 10 treatments are summarized. We took samples after harvest of triticale, in August. We used a reliable method (segmented continuous flow analysis) to determine different (easily mobilized - 0.01 M CaCl2 soluble) N-forms of soil. The 0.01 M CaCl2 soluble inorganic and total N content and the UV digestable organic-N form of soil were determined by this method. The results are summarized below: – The mineralized-N (Nmin.) content of soil increased with dose of nitrogen treatment. Liming treatments increase the amount of Nmin. – The maximum content of easily mobilize organic-N-fraction was found in the upper (0-20 cm) layer. This fact due to the large amount of crop and roots. – Changing of content of 0.01 M CaCl2 soluble total-N-forms due to N doses. – The ratios of these N forms are variable. It is very important that the content of organic N fraction is not negligible and this fraction plays a main role in the plant nutrition.